Material and Theological Identities: A Historical Discourse of Constructions of the Virgin Mary - Bugslag, James (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2009)
AbstractThis article charts, through the longue durée, two contested constructions of the Virgin Mary, the one theological, the other material. Material constructions, founded on such concrete material as relics, images, pilgrimage shrines and sacralized landscape features, differ considerably from, and have sometimes clashed with theological constructions. These two quite distinct hermeneutical strands of Marian identity, I contend, have always formed a discourse, and neither can be understood fully without reference to the other. This discursive consideration of Mary both broadens consideration of her historical identity beyond the hegemonic definition of the Church and creates a fuller appreciation of the diverse functions and meanings that Mary has had for her various constituencies.